How Trade Liberalization Affects a Sugar Dependent Community in Jamaica Global Action, Local Impact - Stanberry, Donovan (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
Located within the plantation economy model of the "New World Group" of The University of the West Indies, this book explores how the changes in the European Union's sugar regime impacted a sugar-dependent community in Jamaica. It details how the end of centuries of preferential treatment of Jamaican sugar in the British/European market in 2005 worsened the social and environmental realities of the Monymusk community in Clarendon, Jamaica, which depended on the sugar industry. In describing the response of the Jamaican Government to the changes in the EU Sugar Regime, and the subsequent roll-out of an EU funded adaptation strategy, the author provides some unique perspectives on this process, drawing on his experience as a senior civil servant involved in the process. The book also highlights the continued social and environmental impact on the area since 2015 . The book concludes with a discussion on the empirical findings and how those findings contribute to the debates on the dependency perpetuated by the Plantation Economy Model of development and the failure of neo-liberal influenced government policies, as well as the lack of imagination of post-independent governments to break this dependency and deliver on the promise of independence.
1 Theoretical Framework -- 2 The Origins and Development of a Plantation Economy -- 3 the Sugar Industry Post-Independence -- 4 The Avalanche of Trade Liberalization Since the 1990s -- 5 The Response -- 6 Conditions of the Industry and the Monymusk Sugar Dependent Area (SDA) before JCS -- 7 The Impact -- 8 Policy Implications.
Keywords: International trade; Development economics; International economic relations; Latin America-Economic conditions; Economic history; International Trade; Development Economics; International Political Economy'.; Latin American/Caribbean Economics; Economic History